Digital Diplomacy Strategy to Win Indonesian Papuan Opinion for National Resilience - Sutoyo; Margaretha Hanita; Eko Daryanto (Journal of Law, Politic and Humanities, 2025)
This paper examines the role of digital diplomacy in countering the propaganda of the Free West Papua movement, which poses a significant threat to Indonesia's national resilience. The study highlights how the Free West Papua movement leverages digital platforms to gain international support and shape public opinion. By analyzing the strategies employed by both the Free West Papua movement and the Indonesian government, this research aims to provide insights into effective counter-propaganda measures through digital diplomacy. This research uses a qualitative descriptive method with an analytical approach, with a focus on the concept of national resilience, threat analysis, and adaptation strategies in the context of digital diplomacy. The findings indicate that the Indonesian government's digital diplomacy efforts need to be enhanced to effectively counter the narratives propagated by the Free West Papua movement. This study proposes a comprehensive digital diplomacy strategy that includes proactive measures to disseminate positive information about Papua, counter misinformation, and engage with international stakeholders. This research contributes to the field of digital diplomacy and national security by providing valuable insights for policymakers and practitioners involved in safeguarding Indonesia's national interests.